The relationships of body mass index, waist-to-height ratio, and body fat percentage with blood pressure and its hemodynamic determinants in Korean adolescents: a school-based study - Na Young Kim; Young Mi Hong; Jo Won Jung; Nam Su Kim; Chung Il Noh; Young-Hwan Song (Korean Pediatric Society, 2013)
PurposeObesity is an important risk factor for hypertension in adolescents. We investigated the relationship of obesity-related indices (body mass index [BMI], waist-to-height ratio [WHR], and body fat percentage [%BF]) with blood pressure and the hemodynamic determinants of blood pressure in Korean adolescents.MethodsIn 2008, 565 adolescents, aged 12-16 years, were examined. The %BF of the participants was measured by bioelectrical impedance analysis. Echocardiography and brachial artery pulse tracing were used to estimate the stroke volume (SV), cardiac output (CO), total vascular resistance (TVR), and total arterial compliance (TAC).ResultsWe noted that BMI, WHR, and %BF were positively correlated with systolic blood pressure (SBP) and diastolic blood pressure (DBP). The positive correlation between BMI and blood pressure (SBP and DBP) persisted after adjustment for WHR and %BF. However, after adjustment for BMI, the positive associations between blood pressure (SBP and DBP) and WHR as well as %BF, were not noted. With regard to the hemodynamic factors, BMI, but not WHR and %BF, was an independent positive factor correlated with SV and CO. TVR had an independent negative association with BMI; however, it was not associated with WHR or %BF. Moreover, we noted that BMI, WHR, and %BF did not affect TAC.ConclusionIn Korean adolescents, BMI had an independent positive correlation with SBP and DBP, possibly because of its effects on SV, CO, and TVR. WHR and %BF are believed to indirectly affect SBP and DBP through changes in BMI.